Three-Direction Type of Diffuser-Shaped Vortex Generator Development for the Wind Solar Tower - Anan Sudsanguan; Amnart Boonloi; Withada Jedsadaratanachai (Energies)
This study explored the use of diffuser shapes to enhance the performance of a solar updraft tower. A diffuser-shaped vortex generator, a simple device requiring no structural modifications to the tower, was installed at the chimney outlet. The generator transformed crosswind into a vortex, increasing the updraft velocity. This study employed finite element methods and numerical models to validate the results alongside physical experiments. Both approaches focused on the crosswind velocity and vortex generator height to determine an optimal semi-opening angle for the diffuser shape. The experimental results revealed that an 8° diffuser-shaped vortex generator with a height of hvg = 2D achieved the greatest updraft enhancement, increasing the speed by 86.89% compared to the prototype tower. The enhancement was found to increase proportionally with the generator’s angle and height.